Effect of Addition of Fine SiC Particles on the Dry Sliding Wear Behaviour of Extruded 2014 Al-Alloy. (16th December 2012) - Dasgupta, Rupa; Jha, A. K.; Das, S.
Abstract : Composites of 2014 alloy made by dispersing 10 vol.% of fine (20–50 µm) SiC particles using vortex method ensuring uniform distribution of SiC particles in the matrix have shown uniform distribution of SiC particles. Mechanical properties of the composites have also registered an improvement over the alloy. In an attempt to further improve the properties, the composites were subjected to hot extrusion of cylindrical rods along with the alloys under similar experimental conditions. A temperature range of 300–350°C and an extrusion ratio of 10 : 1 were maintained during the process. The extruded samples were compared for their mechanical properties, and improvement was noted. The mechanism of material failure from fractographic studies showed difference in behaviour between the alloy and composite. Dry sliding wear studies carried out on extruded specimens exhibited improved wear behaviour in composites over alloys as measured by volume loss and wear rate. Wear mechanism was studied from the worn surface and correlated with the wear performance. It was observed that the presence of SiC particles reduces the tendency of delamination and thus material removal from the wear surface.